2019
DOI: 10.1002/jsfa.9999
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer during osmotic dehydrationand its effect on anthocyanin retention of microwave vacuum‐dried blackberries

Abstract: BACKGROUND: The combination of sugar osmotic dehydration and microwave vacuum drying is an effective method for the dehydration of blackberries, the retention of their antioxidant properties, and the extension of their shelf life. Mass transfer during the osmotic dehydration of blackberries in sugar solution was investigated together with its influence on microwave vacuum drying characteristics, and the retention rate of anthocyanins in dried frozen blackberries. RESULTS:The concentrations of the osmotic solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Moreover, it is also described as a quality improvement and an energy-saving process. Previously, it was reported that applying osmotic pre-treatment prior to microwaveassisted vacuum drying of blackberries results in reduced drying time and increased anthocyanin retention (6). In a study conducted, it was shown that osmotic dehydration improved the colour of apricots after hot air drying (7).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is also described as a quality improvement and an energy-saving process. Previously, it was reported that applying osmotic pre-treatment prior to microwaveassisted vacuum drying of blackberries results in reduced drying time and increased anthocyanin retention (6). In a study conducted, it was shown that osmotic dehydration improved the colour of apricots after hot air drying (7).…”
Section: Introductionmentioning
confidence: 99%
“…[44] Previous research indicated that the antioxidant activity of fruit and vegetables might be ascribed to the presence of specific antioxidant groups, such as ascorbic acid, carotenoids, flavonoids, and phenolic acids . [45][46][47] In this study, the scavenging ability of DPPH, hydroxyl radicals, ABTS, and FRAP, as well as the TFC, TPC, and TAC values, were used to analyze the influence of drying methods on the antioxidant activity of purple cabbage. The scavenging ability of DPPH, hydroxyl radicals, ABTS, and FRAP for cabbage dried using different methods are presented in Table 2.…”
Section: Drying Methods On the Antioxidant Activity Of The Purple Cabbagementioning
confidence: 99%
“…Effective moisture diffusivity (D eff ) is a critical parameter in the modeling, design, and optimization of the drying process. D eff describes the possible mechanisms of movement of water molecules within foodstuff (Dutta et al, 2020;Ozcan-Sinir et al, 2019;Song et al, 2020;Zielinska et al, 2019). The mechanisms include liquid diffusion, vapor diffusion, surface diffusion, capillary flow, hydrodynamic flow, and osmotic dehydration.…”
Section: Introductionmentioning
confidence: 99%